An axillary arch - (:unkn) unknown (Wiley-Liss Inc., 1996)
An axillary (axillopectoral) muscle (arch) was observed extending between the upper border of the latissimus dorsi and the lower border of the pectoralis major muscles in a 48-year-old male cadaver during our dissections. In the same cadaver, the pectoralis major muscle has entirely inserted into the most distal part of the tendon of deltoideus. © 1996 Wiley-Liss, Inc.
Keywords: Axillary arch; Axillary muscle; Axillopectoral muscle